Double-layer composite wire and method for manufacturing high-performance aluminum-based composite material through electromagnetic field regulation and control additive manufacturing of double-layer composite wire
Through the combination method of double-layer composite wire and three-axis electromagnetic field regulation, the problems of uneven reinforcement phase distribution and low interface bonding strength in aluminum-based composite materials are solved, and the preparation of high-performance aluminum-based composite materials is realized, which significantly improves the mechanical properties and corrosion resistance of the material.
Patent Information
- Application Number
- CN202411801088.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The existing aluminum-based composite preparation methods have problems such as uneven enhanced phase distribution, low interfacial bonding strength, and large residual stress, making it difficult to achieve high-performance aluminum-based composite materials.
Using a double-layer composite wire structure and a three-axis electromagnetic field regulation additive manufacturing method, the in-situ generation of TiB2 nanophase and the full solid solution of Cu-Mg elements is achieved by precisely controlling the composition and microstructure of the core Al-Ti-B alloy and the shell Al-Cu-Mg alloy.
The mechanical properties, corrosion resistance and process adaptability of aluminum-based composite materials have been significantly improved, and the synergy between nano-reinforced phase and solid solution strengthening has been achieved, solving the problem of improving material performance.
Smart Images

Figure BDA0005178067300000191 
Figure BDA0005178067300000192 
Figure BDA0005178067300000201
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum-based composite materials, and in particular to a double-layer composite wire material and a method for manufacturing a high-performance aluminum-based composite material by electromagnetic field control additive manufacturing. Background Art
[0002] With the growing demand for high-performance lightweight materials in aerospace, automotive industry, and electronic packaging, aluminum-based composites have attracted widespread attention due to their excellent specific strength and specific modulus. However, the traditional preparation methods of aluminum-based composites face many challenges, such as uneven distribution of reinforcement phase, low interface bonding strength, and large residual stress, which seriously restrict the further improvement of material performance.
[0003] In recent years, the rapid development of additive manufacturing technology has provided a new way to prepare high-performance metal materials. However, existing metal additive manufacturing technology still has many limitations when processing aluminum-based composite materials. First, it is difficult to achieve precise control of multiple components in traditional single-layer alloy wires, resulting in uneven distribution of the reinforcement phase. Secondly, in the conventional laser cladding process, the flow behavior of the molten pool is difficult to accurately control, which not only affects the distribution of the reinforcement phase, but also easily leads to the formation of defects such as pores and cracks. In addition, it is difficult for existing technologies to simultaneously achieve uniform distribution of nano-reinforcement phases and sufficient solid solution of matrix alloy elements, which limits the material strengthening effect.
[0004] In view of the above problems, a new preparation method is urgently needed to achieve precise design and control of the microstructure of aluminum-based composite materials and improve the comprehensive performance of the materials. The present invention is proposed in this context, aiming to break through the limitations of the existing technology and provide an innovative solution for the preparation of high-performance aluminum-based composite materials. Summary of the invention
[0005] The core innovation of the invention lies in the unique combination of a double-layer composite wire structure and a three-axis electromagnetic field controlled additive manufacturing method. This innovative design not only overcomes many difficulties in the existing technology, but also brings a series of unexpected technical effects.
[0006] The object of the present invention is to provide a double-layer composite wire and a method for manufacturing a high-performance aluminum-based composite material by electromagnetic field control additive manufacturing, comprising the following steps:
[0007] (1) preparing a double-layer composite wire;
[0008] (2) Using three-axis electromagnetic fields to control the additive manufacturing process;
[0009] (3) Post-processing the prepared aluminum-based composite material.
[0010] Preferably, the method for preparing the double-layer composite wire in step (1) comprises:
[0011] (a) preparing a core alloy, comprising the following steps:
[0012] First, a pure aluminum ingot with a purity of ≥99.99% is placed in a graphite crucible and heated to 700-750°C for melting under argon protection;
[0013] Secondly, add a predetermined amount of titanium powder with a purity of ≥99.5% and boron powder with a purity of ≥99.5%, stir at a speed of 300-400 rpm, and keep for 30-60 minutes;
[0014] Then, the melt is poured into a metal mold preheated to 200-250°C and cooled to room temperature;
[0015] (b) preparing a shell alloy, comprising the following steps:
[0016] First, a pure aluminum ingot with a purity of ≥99.99% is placed in another graphite crucible and heated to 700-750°C for melting under argon protection;
[0017] Secondly, add predetermined amounts of copper particles with a purity of ≥99.9% and magnesium ingots with a purity of ≥99.9% in sequence, stir at a speed of 300-400 rpm, and keep stirring for 20-40 minutes;
[0018] Then, the melt is poured into a metal mold preheated to 200-250°C and cooled to room temperature;
[0019] (c) processing the core alloy and the shell alloy into round rods with a diameter of 8-10 mm respectively;
[0020] (d) processing the shell alloy round rod into a hollow round tube having an inner diameter slightly larger than the diameter of the core alloy round rod;
[0021] (e) inserting the core alloy round rod into the shell alloy hollow round tube to ensure that the two fit tightly;
[0022] (f) placing the assembled double-layer structure in a vacuum hot isostatic pressing device at 500-550° C. and a pressure of 100-150 MPa for 2-4 hours;
[0023] (g) The double-layer composite material after hot isostatic pressing is subjected to multiple hot extrusion and cold stretching to finally obtain a double-layer composite wire with a diameter of 1.2-1.6 mm.
[0024] Preferably, the composition of the core alloy is:
[0025] Aluminum: 92.5-96.0% by weight
[0026] Titanium: 3.0-6.0% by weight
[0027] Boron: 0.5-1.5 wt%.
[0028] Preferably, the composition of the shell alloy is:
[0029] Aluminum: 93.0-96.5% by weight
[0030] Copper: 2.5-5.0% by weight
[0031] Magnesium: 1.0-2.5% by weight.
[0032] Preferably, the step (2) of using a three-axis electromagnetic field to control the additive manufacturing process includes the following steps:
[0033] (a) Equipment preparation:
[0034] A fiber laser with a power of 1000-1500W is used as a heat source;
[0035] Design and install a three-axis electromagnetic field generator that can independently generate a magnetic field strength of 0.2-0.5T in the x, y, and z directions;
[0036] Prepare an additive manufacturing molding chamber with inert gas protection function;
[0037] (b) Process parameter setting:
[0038] Laser power: 800-1200W;
[0039] Scanning speed: 600-1000mm / min;
[0040] Wire feeding speed: 1500-2500mm / min;
[0041] Layer thickness: 0.2-0.4mm;
[0042] Argon flow rate: 15-25L / min;
[0043] Substrate preheating temperature: 150-200℃;
[0044] (c) Electromagnetic field parameter settings:
[0045] X-axis magnetic field strength: 0.2-0.3T;
[0046] Y-axis magnetic field strength: 0.3-0.4T;
[0047] z-axis magnetic field strength: 0.4-0.5T;
[0048] Magnetic field frequency: 10-50Hz;
[0049] (d) Manufacturing process:
[0050] First, the double-layer composite wire is loaded into the wire feeding device;
[0051] Secondly, start the inert gas protection system to fill the molding chamber with argon gas; then, preheat the substrate to the set temperature;
[0052] Again, start the three-axis electromagnetic field system;
[0053] Next, the laser scanning and wire feeding process begins, and deposition is performed layer by layer. After each layer is deposited, a cooling time of 20-30 seconds is maintained.
[0054] Repeat the above process until the entire part is manufactured.
[0055] Preferably, the post-treatment in step (3) comprises the following steps: (a) cooling the manufactured part to room temperature in an inert gas environment; (b) performing T6 heat treatment, comprising:
[0056] Solution treatment: 530-550℃, hold for 1-2 hours;
[0057] Quenching: water quenching to room temperature;
[0058] Aging treatment: 160-180℃, keep for 6-8 hours.
[0059] Preferably, the method further comprises the following control points:
[0060] (a) TiB 2 In-situ build control:
[0061] Reaction temperature: 700-750℃;
[0062] Reaction time: 30-60 minutes;
[0063] Stirring speed: 300-400rpm;
[0064] Cooling rate:>50℃ / s;
[0065] (b) Cu-Mg solid solution strengthening control:
[0066] Solution treatment temperature: 530-550℃;
[0067] Solution time: 1-2 hours;
[0068] Quenching medium: water (temperature: 20-25°C);
[0069] Aging temperature: 160-180℃;
[0070] Aging time: 6-8 hours;
[0071] (c) Electromagnetic field regulation:
[0072] Magnetic field strength range: 0.2-0.5T;
[0073] Magnetic field frequency: 10-50Hz;
[0074] Magnetic field direction: x, y, z three-axis independent control;
[0075] Magnetic field waveform: sine wave;
[0076] (d) Porosity control:
[0077] Inert gas purity: ≥99.999%;
[0078] Gas flow rate: 15-25L / min;
[0079] Molding chamber pressure: 1.1-1.2 standard atmospheres;
[0080] Molten pool temperature: 660-720℃.
[0081] Preferably, the method further comprises the following steps:
[0082] During the additive manufacturing process, after each layer of deposition is completed, an eddy current flaw detector is used to perform real-time non-destructive testing of the deposited layer with a detection frequency of 1-5MHz and a scanning speed of 50-100mm / s.
[0083] Preferably, the method further comprises the following steps:
[0084] After T6 heat treatment, the obtained aluminum matrix composite material is subjected to surface treatment, including:
[0085] First, sandblasting was performed using alumina sand with a particle size of 80-120 mesh and a sandblasting pressure of 0.4-0.6MPa;
[0086] Secondly, anodization treatment was performed in a 20wt% sulfuric acid solution at a current density of 1-2A / dm 2 , the temperature is 18-22℃, the time is 30-60 minutes;
[0087] Finally, seal the holes by soaking in boiling water for 15-30 minutes.
[0088] Preferably, the method further comprises the following steps:
[0089] During the additive manufacturing process, a high-speed camera is used to monitor the molten pool status in real time. The camera frame rate is 1000-2000fps and the resolution is not less than 1280x1024 pixels. The laser power and wire feeding speed are adjusted in real time based on the image analysis results, and the adjustment frequency is 10-20Hz.
[0090] First, the design of the double-layer composite wire cleverly solves the problem of precise control of multiple components. The core Al-Ti-B alloy is TiB 2 The in-situ generation of the nanophase provides an ideal reaction environment, while the shell Al-Cu-Mg alloy provides solid solution strengthening elements for the matrix. This hierarchical design not only achieves the spatial separation of the reinforcing phase and solid solution strengthening elements, but also creates conditions for the synergistic effect of the two strengthening mechanisms.
[0091] Secondly, the introduction of three-axis electromagnetic field control technology provides a powerful tool for precise control of molten pool behavior. By independently controlling the magnetic field intensity and frequency in the x, y, and z directions, multi-dimensional control of molten pool flow, heat transfer, and solidification behavior can be achieved. This not only helps TiB 2 The uniform distribution of nanophase can also promote the full diffusion and solid solution of Cu and Mg elements. More importantly, the electromagnetic field-induced molten pool convection significantly improves the gas exhaust efficiency and effectively reduces the porosity of the material.
[0092] From the perspective of materials science, the method of the present invention achieves the synergistic effect of nano-reinforced phase and solid solution strengthening. 2 The nanophase not only directly provides particle reinforcement effect, but also improves material strength by pinning dislocations and refining grains. 2 The nanophase provides a preferential channel for the diffusion of Cu and Mg atoms, accelerating the formation of solid solution. This synergistic effect on microstructure is difficult to achieve with traditional preparation methods.
[0093] From the perspective of chemical mechanism, the present invention makes full use of the thermodynamic and kinetic characteristics of the Al-Ti-B system. In the high-temperature molten pool, Ti and B atoms form TiB through a complex diffusion and nucleation process. 2 The presence of electromagnetic field not only affects the diffusion behavior of Ti and B atoms, but also may affect the TiB 2 At the same time, the solid solution process of Cu and Mg atoms in the Al matrix is also regulated by the electromagnetic field, which may form a more complex point defect structure, thereby enhancing the solid solution strengthening effect.
[0094] Another significant advantage of the present invention is the adjustability and adaptability of its process. By precisely controlling the composition ratio of the double-layer wire, the electromagnetic field parameters and the post-processing process, the performance of the material can be customized according to specific application requirements. This high degree of designability provides broad space for the development of a new generation of high-performance aluminum-based composite materials.
[0095] In summary, the present invention successfully solves several key problems in the prior art through innovative material design and process control, and realizes the precise preparation of high-performance aluminum-based composite materials. This method not only significantly improves the mechanical properties and corrosion resistance of the material, but also has good process adaptability and scalability. Therefore, the present invention provides a highly potential new material preparation solution for the fields of aerospace, automotive industry, and electronic packaging, and is expected to promote technological innovation and upgrading of related industries. DETAILED DESCRIPTION
[0096] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0097] Example 1
[0098] This embodiment provides a double-layer composite wire and a method for manufacturing a high-performance aluminum-based composite material by electromagnetic field control additive manufacturing. The method includes the following steps:
[0099] (1) Preparation of double-layer composite wire
[0100] First, prepare the core alloy. Place a pure aluminum ingot with a purity of 99.99% in a graphite crucible and heat it to 700°C under argon protection to melt. Then, add 3.0 wt% of titanium powder with a purity of 99.5% and 0.5 wt% of boron powder with a purity of 99.5%, stir at a speed of 300 rpm, and keep it for 30 minutes. This step is to promote TiB 2 The in-situ generation of the nanophase provides the material with a reinforcement phase with high strength and high modulus. The melt is then poured into a metal mold preheated to 200°C and cooled to room temperature.
[0101] Secondly, prepare the shell alloy. Place a pure aluminum ingot with a purity of 99.99% in another graphite crucible and heat it to 750°C under argon protection to melt. Add 2.5% by weight of copper particles with a purity of 99.9% and 1.0% by weight of magnesium ingots with a purity of 99.9% in turn, stir at a speed of 400rpm, and keep for 20 minutes. The addition of Cu and Mg is intended to achieve solid solution strengthening and improve the strength and hardness of the material. Pour the melt into a metal mold preheated to 250°C and cool to room temperature.
[0102] Next, the core alloy and the shell alloy are processed into round rods with a diameter of 8 mm. The shell alloy round rod is processed into a hollow round tube with an inner diameter slightly larger than the diameter of the core alloy round rod. The core alloy round rod is inserted into the shell alloy hollow round tube to ensure that the two fit tightly. This core-shell structure design is conducive to the TiB 2 Uniform distribution of phases and synergistic effect of Cu-Mg solid solution strengthening.
[0103] Then, the assembled double-layer structure was placed in a vacuum hot isostatic pressing device and maintained at 500°C and 100 MPa for 2 hours to achieve metallurgical bonding of the two layers of alloy. Finally, the double-layer composite material after hot isostatic pressing was subjected to multiple hot extrusion and cold stretching to finally produce a double-layer composite wire with a diameter of 1.2 mm.
[0104] (2) Using three-axis electromagnetic fields to control the additive manufacturing process
[0105] In this step, a fiber laser with a power of 1000W is first used as a heat source. A three-axis electromagnetic field generator is designed and installed, which can independently generate magnetic field strength in the x, y, and z directions. An additive manufacturing molding chamber with inert gas protection function is prepared.
[0106] The process parameters are set as follows: laser power is 800W, scanning speed is 600mm / min, wire feeding speed is 1500mm / min, layer thickness is 0.2mm, argon flow rate is 15L / min, and substrate preheating temperature is 150℃. The electromagnetic field parameters are set as follows: x-axis magnetic field strength is 0.2T, y-axis magnetic field strength is 0.3T, z-axis magnetic field strength is 0.4T, and magnetic field frequency is 10Hz. The precise control of these parameters is aimed at optimizing the molten pool behavior, promoting the uniform distribution of TiB2 nanophase and the full solid solution of Cu-Mg elements.
[0107] The manufacturing process is as follows: First, the double-layer composite wire is loaded into the wire feeding device. Second, the inert gas protection system is started to fill the molding chamber with argon. Then, the substrate is preheated to the set temperature. Third, the three-axis electromagnetic field system is started. Next, the laser scanning and wire feeding process are started to deposit layer by layer. After each layer is deposited, a cooling time of 20 seconds is maintained. The above process is repeated until the entire part is manufactured.
[0108] (3) Post-processing of the prepared aluminum-based composite material
[0109] The manufactured parts are cooled to room temperature in an inert gas environment. Then they are subjected to T6 heat treatment, including solution treatment (530°C, hold for 1 hour), water quenching to room temperature, and aging treatment (160°C, hold for 6 hours). This heat treatment process is designed to further optimize the microstructure of the material and improve its strength and toughness.
[0110] Preferably, in the embodiment of the present invention, during the additive manufacturing process, after each layer of deposition is completed, an eddy current flaw detector is used to perform real-time nondestructive testing on the deposited layer, with a detection frequency of 1 MHz and a scanning speed of 50 mm / s. This step helps to timely discover and correct defects that may occur in the manufacturing process, and improve the quality consistency of the final product.
[0111] Example 2
[0112] This embodiment provides another double-layer composite wire material and a method for manufacturing a high-performance aluminum-based composite material by electromagnetic field control. The method comprises the following steps:
[0113] (1) Preparation of double-layer composite wire
[0114] First, prepare the core alloy. Place a pure aluminum ingot with a purity of 99.99% in a graphite crucible and heat it to 725°C under argon protection to melt. Then, add 4.5% by weight of titanium powder with a purity of 99.5% and 1.0% by weight of boron powder with a purity of 99.5%, stir at a speed of 350rpm, and keep it for 45 minutes. This ratio is intended to increase TiB 2 The volume fraction of the nanophase further improves the strength and wear resistance of the material. Then, the melt is poured into a metal mold preheated to 225°C and cooled to room temperature.
[0115] Secondly, prepare the shell alloy. Place a pure aluminum ingot with a purity of 99.99% in another graphite crucible and heat it to 725°C under argon protection to melt. Add 3.75% by weight of copper particles with a purity of 99.9% and 1.75% by weight of magnesium ingots with a purity of 99.9% in turn, stir at a speed of 350rpm, and keep for 30 minutes. This ratio is intended to enhance the Cu-Mg solid solution strengthening effect while maintaining good plasticity. Pour the melt into a metal mold preheated to 225°C and cool to room temperature.
[0116] Next, the core alloy and the shell alloy are processed into round rods with a diameter of 9 mm respectively. The shell alloy round rod is processed into a hollow round tube with an inner diameter slightly larger than the diameter of the core alloy round rod. The core alloy round rod is inserted into the shell alloy hollow round tube to ensure that the two fit tightly.
[0117] Then, the assembled double-layer structure was placed in a vacuum hot isostatic pressing device and maintained at 525°C and 125 MPa for 3 hours to achieve metallurgical bonding of the two layers of alloy. Finally, the double-layer composite material after hot isostatic pressing was subjected to multiple hot extrusion and cold drawing to finally produce a double-layer composite wire with a diameter of 1.4 mm.
[0118] (2) Using three-axis electromagnetic fields to control the additive manufacturing process
[0119] In this step, a fiber laser with a power of 1250W is first used as a heat source. A three-axis electromagnetic field generator is designed and installed, which can independently generate magnetic field strength in the x, y, and z directions. An additive manufacturing molding chamber with inert gas protection is prepared.
[0120] The process parameters are set as follows: laser power is 1000W, scanning speed is 800mm / min, wire feeding speed is 2000mm / min, layer thickness is 0.3mm, argon flow rate is 20L / min, substrate preheating temperature is 175℃. The electromagnetic field parameters are set as follows: x-axis magnetic field strength is 0.25T, y-axis magnetic field strength is 0.35T, z-axis magnetic field strength is 0.45T, and magnetic field frequency is 30Hz. The adjustment of these parameters is aimed at optimizing the kinetic behavior of the molten pool and improving the TiB 2 Dispersion uniformity of nanophase and diffusion rate of Cu-Mg elements.
[0121] The manufacturing process is as follows: First, the double-layer composite wire is loaded into the wire feeding device. Secondly, the inert gas protection system is started to fill the molding chamber with argon. Then, the substrate is preheated to the set temperature. Again, the three-axis electromagnetic field system is started. Next, the laser scanning and wire feeding process are started to deposit layer by layer. After each layer is deposited, a cooling time of 25 seconds is maintained. The above process is repeated until the entire part is manufactured.
[0122] (3) Post-processing of the prepared aluminum-based composite material
[0123] The manufactured parts are cooled to room temperature in an inert gas environment. Then T6 heat treatment is carried out, including: solution treatment (540℃, hold for 1.5 hours), water quenching to room temperature, and aging treatment (170℃, hold for 7 hours). This heat treatment process is designed to fully utilize the potential of Cu-Mg solid solution strengthening while maintaining TiB 2 Stability of the nanophase.
[0124] Preferably, in the embodiment of the present invention, the aluminum-based composite material obtained can also be subjected to surface treatment after T6 heat treatment. First, sandblasting is performed, using alumina sand with a particle size of 100 mesh and a sandblasting pressure of 0.5 MPa. Second, anodizing is performed in a 20wt% sulfuric acid solution at a current density of 1.5A / dm 2 , temperature is 20℃, time is 45 minutes. Finally, sealing treatment is carried out, soaking in boiling water for 22 minutes. This series of surface treatments is aimed at improving the corrosion resistance and surface hardness of the material, and expanding its application potential in harsh environments.
[0125] Example 3
[0126] This embodiment provides a third double-layer composite wire material and a method for manufacturing a high-performance aluminum-based composite material by electromagnetic field control additive manufacturing. The method comprises the following steps:
[0127] (1) Preparation of double-layer composite wire
[0128] First, the core alloy was prepared. A pure aluminum ingot with a purity of 99.99% was placed in a graphite crucible and heated to 750°C under argon protection to melt. Subsequently, 6.0 wt% of 99.5% pure titanium powder and 1.5 wt% of 99.5% pure boron powder were added, and the stirring speed was 400 rpm for 60 minutes. This ratio and process parameters are designed to maximize the TiB 2 The amount of nanophase generated significantly improves the strength and rigidity of the material. The melt is then poured into a metal mold preheated to 250°C and cooled to room temperature.
[0129] Secondly, prepare the shell alloy. Place a pure aluminum ingot with a purity of 99.99% in another graphite crucible and heat it to 700°C under argon protection to melt. Add 5.0% by weight of copper particles with a purity of 99.9% and 2.5% by weight of magnesium ingots with a purity of 99.9% in turn, stir at a speed of 300rpm, and keep for 40 minutes. This ratio is designed to achieve the strongest Cu-Mg solid solution strengthening effect, while balancing strength and toughness by controlling the stirring speed and time. Pour the melt into a metal mold preheated to 200°C and cool to room temperature.
[0130] Next, the core alloy and the shell alloy are processed into round bars with a diameter of 10 mm respectively. The shell alloy round bar is processed into a hollow round tube with an inner diameter slightly larger than the diameter of the core alloy round bar. The core alloy round bar is inserted into the shell alloy hollow round tube to ensure that the two fit tightly.
[0131] Then, the assembled double-layer structure was placed in a vacuum hot isostatic pressing device at 550°C and 150 MPa for 4 hours to achieve metallurgical bonding of the two layers of alloy. This process parameter is designed to ensure a stable metallurgical bond between the two layers of alloy while avoiding TiB 2 Finally, the double-layer composite material after hot isostatic pressing was subjected to multiple hot extrusion and cold drawing to finally obtain a double-layer composite wire with a diameter of 1.6 mm.
[0132] (2) Using three-axis electromagnetic fields to control the additive manufacturing process
[0133] In this step, a fiber laser with a power of 1500W is first used as a heat source. A three-axis electromagnetic field generator is designed and installed, which can independently generate magnetic field strength in the x, y, and z directions. An additive manufacturing molding chamber with inert gas protection is prepared.
[0134] The process parameters are set as follows: laser power is 1200W, scanning speed is 1000mm / min, wire feeding speed is 2500mm / min, layer thickness is 0.4mm, argon flow rate is 25L / min, substrate preheating temperature is 200℃. The electromagnetic field parameters are set as follows: x-axis magnetic field strength is 0.3T, y-axis magnetic field strength is 0.4T, z-axis magnetic field strength is 0.5T, and magnetic field frequency is 50Hz. These parameters are set to maximize the effect of electromagnetic field on the behavior of the molten pool and promote TiB 2 The uniform distribution of nanophase and sufficient diffusion of Cu-Mg elements, while the high-frequency electromagnetic field is used to refine the solidification structure.
[0135] The manufacturing process is as follows: First, the double-layer composite wire is loaded into the wire feeding device. Second, the inert gas protection system is started to fill the molding chamber with argon. Then, the substrate is preheated to the set temperature. Again, the three-axis electromagnetic field system is started. Next, the laser scanning and wire feeding process are started to deposit layer by layer. After each layer is deposited, a cooling time of 30 seconds is maintained. The above process is repeated until the entire part is manufactured.
[0136] (3) Post-processing of the prepared aluminum-based composite material
[0137] The manufactured parts are cooled to room temperature in an inert gas environment. Then T6 heat treatment is carried out, including: solution treatment (550°C, hold for 2 hours), water quenching to room temperature, and aging treatment (180°C, hold for 8 hours). This heat treatment process parameter is designed to fully dissolve Cu and Mg elements to form a large amount of strengthening phases, while achieving the best strength-toughness balance through long-term aging treatment.
[0138] Preferably, in the embodiment of the present invention, a high-speed camera can be used to monitor the state of the molten pool in real time during the additive manufacturing process, with a camera frame rate of 2000fps and a resolution of 1280x1024 pixels, and the laser power and wire feeding speed can be adjusted in real time based on the image analysis results, with an adjustment frequency of 20Hz. This real-time monitoring and feedback system can significantly improve the stability and controllability of the manufacturing process, and further improve the quality consistency of the final product.
[0139] Example 4
[0140] This embodiment provides a fourth double-layer composite wire material and a method for manufacturing a high-performance aluminum-based composite material by electromagnetic field control additive manufacturing. The method comprises the following steps:
[0141] (1) Preparation of double-layer composite wire
[0142] First, prepare the core alloy. Place a pure aluminum ingot with a purity of 99.99% in a graphite crucible and heat it to 725°C under argon protection to melt. Then, add 4.5% by weight of titanium powder with a purity of 99.5% and 1.0% by weight of boron powder with a purity of 99.5% and stir at a speed of 350 rpm for 45 minutes. This ratio and process parameters are designed to achieve TiB 2 The optimal size distribution of the nanophase (20-50nm) is achieved to obtain the desired strengthening effect. The melt is then poured into a metal mold preheated to 225°C and cooled to room temperature.
[0143] Secondly, prepare the shell alloy. Place a pure aluminum ingot with a purity of 99.99% in another graphite crucible and heat it to 725°C under argon protection to melt. Add 3.75% by weight of copper particles with a purity of 99.9% and 1.75% by weight of magnesium ingot with a purity of 99.9% in turn, stir at a speed of 350rpm, and keep it for 30 minutes. This ratio is intended to achieve Cu-Mg solid solution strengthening and TiB 2 The best synergistic effect of nanophase reinforcement. The melt was poured into a metal mold preheated to 225°C and cooled to room temperature.
[0144] Next, the core alloy and the shell alloy are processed into round rods with a diameter of 9 mm respectively. The shell alloy round rod is processed into a hollow round tube with an inner diameter slightly larger than the diameter of the core alloy round rod. The core alloy round rod is inserted into the shell alloy hollow round tube to ensure that the two fit tightly.
[0145] Then, the assembled double-layer structure was placed in a vacuum hot isostatic pressing device and maintained at 525°C and 125 MPa for 3 hours to achieve metallurgical bonding of the two layers of alloy. This process parameter is designed to ensure that the two layers of alloy are fully bonded while avoiding TiB 2 The excessive growth of nanophase and the excessive diffusion of Cu-Mg elements. Finally, the double-layer composite material after hot isostatic pressing was subjected to multiple hot extrusion and cold drawing to finally obtain a double-layer composite wire with a diameter of 1.4 mm.
[0146] (2) Using three-axis electromagnetic fields to control the additive manufacturing process
[0147] In this step, a fiber laser with a power of 1250W is first used as a heat source. A three-axis electromagnetic field generator is designed and installed, which can independently generate magnetic field strength in the x, y, and z directions. An additive manufacturing molding chamber with inert gas protection is prepared.
[0148] The process parameters are set as follows: laser power is 1000W, scanning speed is 800mm / min, wire feeding speed is 2000mm / min, layer thickness is 0.3mm, argon flow rate is 20L / min, substrate preheating temperature is 175℃. The electromagnetic field parameters are set as follows: x-axis magnetic field strength is 0.25T, y-axis magnetic field strength is 0.35T, z-axis magnetic field strength is 0.45T, and magnetic field frequency is 30Hz. These parameters are set to achieve the best flow state of the fluid inside the molten pool and promote TiB 2 The uniform distribution of nanophase and sufficient diffusion of Cu-Mg elements, while the solidification structure is refined through electromagnetic stirring.
[0149] The manufacturing process is as follows: First, the double-layer composite wire is loaded into the wire feeding device. Secondly, the inert gas protection system is started to fill the molding chamber with argon. Then, the substrate is preheated to the set temperature. Again, the three-axis electromagnetic field system is started. Next, the laser scanning and wire feeding process are started to deposit layer by layer. After each layer is deposited, a cooling time of 25 seconds is maintained. The above process is repeated until the entire part is manufactured.
[0150] (3) Post-processing of the prepared aluminum-based composite material
[0151] The manufactured parts are cooled to room temperature in an inert gas environment. Then T6 heat treatment is carried out, including: solution treatment (540℃, hold for 1.5 hours), water quenching to room temperature, and aging treatment (170℃, hold for 7 hours). This heat treatment process parameter is designed to achieve the best precipitation state of Cu-Mg solid solution strengthening phase while maintaining TiB 2 The stability of the nanophase results in an optimal balance of strength and toughness.
[0152] Preferably, in an embodiment of the present invention, the following control measures may also be implemented in the additive manufacturing process:
[0153] a) TiB 2 In-situ generation control: reaction temperature 725℃, reaction time 45 minutes, stirring speed 350rpm, cooling rate 70℃ / s. Precise control of these parameters helps to obtain TiB with ideal size and distribution. 2 Nanophase.
[0154] b) Cu-Mg solid solution strengthening control: solid solution treatment temperature 540℃, solid solution time 1.5 hours, quenching medium is 22℃ water, aging temperature 170℃, aging time 7 hours. This process is designed to achieve the best solid solution strengthening effect of Cu-Mg elements.
[0155] c) Electromagnetic field control: The magnetic field intensity range is 0.25-0.45T, the magnetic field frequency is 30Hz, the magnetic field directions x, y, and z are independently controlled, and the magnetic field waveform is a sine wave. This electromagnetic field configuration can effectively control the behavior of the molten pool, promote gas discharge and microstructure refinement.
[0156] d) Porosity control: inert gas purity 99.999%, gas flow 20L / min, molding chamber pressure 1.15 standard atmospheres, molten pool temperature 690°C. Precise control of these parameters helps reduce the porosity to below 0.3%, significantly improving the mechanical properties and service life of the material.
[0157] Comparative Example 1: Single-layer aluminum alloy wire and conventional additive manufacturing method thereof
[0158] This comparative example is intended to verify the superiority of the double-layer composite wire structure and is compared with Example 1. The method comprises the following steps:
[0159] (1) Preparation of single-layer aluminum alloy wire
[0160] First, a pure aluminum ingot with a purity of 99.99% was placed in a graphite crucible and heated to 725°C under argon protection to melt. Subsequently, 3.0 wt% of titanium powder with a purity of 99.5%, 0.5 wt% of boron powder with a purity of 99.5%, 2.5 wt% of copper particles with a purity of 99.9% and 1.0 wt% of magnesium ingot with a purity of 99.9% were added, and the stirring speed was 350 rpm for 40 minutes. This step is intended to mix the components of the core and shell alloys together to verify the necessity of the double-layer structure.
[0161] The melt was then poured into a metal mold preheated to 225°C and cooled to room temperature. Next, the alloy was processed into a round rod with a diameter of 9 mm, and through multiple hot extrusion and cold drawing, a single-layer alloy wire with a diameter of 1.2 mm was finally produced.
[0162] (2) Conventional additive manufacturing process
[0163] In this step, a fiber laser with a power of 1000 W is used as a heat source, but electromagnetic field regulation is not used. The process parameter settings are the same as those in Example 1, but electromagnetic field related parameters are not included.
[0164] The manufacturing process is as follows: First, a single layer of alloy wire is loaded into the wire feeding device. Second, the inert gas protection system is started to fill the molding chamber with argon gas. Then, the substrate is preheated to the set temperature. Next, the laser scanning and wire feeding process are started to deposit layer by layer. After each layer is deposited, a cooling time of 20 seconds is maintained. The above process is repeated until the entire part is manufactured.
[0165] (3) Post-processing
[0166] The post-processing steps are the same as in Example 1.
[0167] By comparison with Example 1, it can be found that the single-layer alloy wire cannot achieve the local distribution of TiB2 phase and the gradient distribution of Cu-Mg elements, resulting in the reinforcement effect being less significant than that of the double-layer structure. At the same time, the lack of electromagnetic field regulation also makes it difficult to accurately control the behavior of the molten pool, which may lead to increased porosity and uneven structure.
[0168] Comparative Example 2: Double-layer composite wire and its uniaxial electromagnetic field controlled additive manufacturing method
[0169] This comparative example is intended to verify the necessity of three-axis electromagnetic field regulation and is compared with Example 2. The method comprises the following steps:
[0170] (1) Preparation of double-layer composite wire
[0171] The preparation method of the double-layer composite wire is exactly the same as that of Example 2.
[0172] (2) Single-axis electromagnetic field control of additive manufacturing process
[0173] In this step, a fiber laser with a power of 1250 W is used as a heat source, but only a single-axis (z-axis) electromagnetic field is used for regulation. The process parameter settings are the same as those in Example 2, but the electromagnetic field parameters only retain the z-axis magnetic field intensity of 0.45 T and the magnetic field frequency of 30 Hz.
[0174] The manufacturing process is similar to that of Example 2, but only the z-axis electromagnetic field system is activated.
[0175] (3) Post-processing
[0176] The post-processing steps are the same as those in Example 2.
[0177] By comparing with Example 2, it can be observed that the uniaxial electromagnetic field regulation cannot achieve precise control of the three-dimensional flow of the molten pool, resulting in the TiB 2 The uniformity of the nanophase distribution is reduced, and the diffusion of Cu-Mg elements is not as sufficient as that regulated by the three-axis electromagnetic field. This comparison highlights the important role of the three-axis electromagnetic field in optimizing the microstructure of materials.
[0178] Comparative Example 3: Double-layer composite wire and high-power laser additive manufacturing method thereof
[0179] This comparative example is intended to verify the importance of appropriate laser power and electromagnetic field intensity, and is compared with Example 3. The method comprises the following steps:
[0180] (1) Preparation of double-layer composite wire
[0181] The preparation method of the double-layer composite wire is exactly the same as that of Example 3.
[0182] (2) High-power laser additive manufacturing process
[0183] In this step, a fiber laser with a power of 2000W is used as a heat source, which greatly increases the laser power. The process parameters are set as follows: laser power is 1800W, scanning speed is 1200mm / min, wire feeding speed is 3000mm / min, and other parameters are the same as those in Example 3. The electromagnetic field parameters are set as follows: x-axis magnetic field strength is 0.4T, y-axis magnetic field strength is 0.5T, z-axis magnetic field strength is 0.6T, and magnetic field frequency is 70Hz.
[0184] The fabrication process is similar to that of Example 3, but with higher laser power and electromagnetic field strength.
[0185] (3) Post-processing
[0186] The post-processing steps are the same as those in Example 3.
[0187] By comparing with Example 3, it can be found that excessively high laser power and electromagnetic field intensity may lead to excessively high molten pool temperature, causing TiB 2 The nanophase grows, reducing its strengthening effect. At the same time, an overly strong electromagnetic field may cause the molten pool to flow too violently, affecting the formation of the solidification structure. This comparison highlights the importance of accurately controlling the process parameters in the present invention.
[0188] Comparative Example 4: Double-layer composite wire and additive manufacturing method thereof without inert gas protection
[0189] This comparative example is intended to verify the necessity of inert gas protection and is compared with Example 4. The method comprises the following steps:
[0190] (1) Preparation of double-layer composite wire
[0191] The preparation method of the double-layer composite wire is exactly the same as that of Example 4.
[0192] (2) No inert gas protection for additive manufacturing process
[0193] In this step, the process parameters are set the same as those in Example 4, but inert gas protection is not used. The manufacturing process is carried out in air, and the other steps are similar to those in Example 4.
[0194] (3) Post-processing
[0195] The post-processing steps are the same as those in Example 4.
[0196] By comparing with Example 4, it can be observed that the lack of inert gas protection will cause the material to be severely oxidized at high temperature, forming a large number of oxide inclusions, which significantly reduces the mechanical properties of the material. At the same time, the oxidation reaction will interfere with the TiB 2The in-situ generation of Cu and the solid solution process of Cu-Mg elements affect the strengthening effect of the material. This comparison highlights the key role of inert gas protection in ensuring material quality.
[0197] Comparative Example 5: Double-layer composite wire and additive manufacturing method without post-processing
[0198] This comparative example is intended to verify the importance of post-treatment (especially T6 heat treatment) and is compared with Example 1. The method comprises the following steps:
[0199] (1) Preparation of double-layer composite wire
[0200] The preparation method of the double-layer composite wire is exactly the same as that in Example 1.
[0201] (2) Electromagnetic field control of additive manufacturing process
[0202] The additive manufacturing process is exactly the same as in Example 1.
[0203] (3) No post-processing
[0204] All post-treatment steps, including the T6 heat treatment, were omitted in this comparative example.
[0205] By comparison with Example 1, it can be found that the lack of T6 heat treatment will greatly reduce the Cu-Mg solid solution strengthening effect, and the strength and hardness of the material are significantly lower than those of the heat-treated samples. At the same time, the samples without heat treatment may have higher residual stress, affecting the stability and service life of the material. This comparison highlights the important role of post-treatment in optimizing material properties.
[0206] Comparative Example 6: Double-layer composite wire with high Ti and B content and its electromagnetic field controlled additive manufacturing method
[0207] This comparative example aims to verify the effect of appropriate Ti and B contents on TiB 2 The importance of nanophase formation is compared with Example 2. The method comprises the following steps:
[0208] (1) Preparation of high Ti and B content double-layer composite wire
[0209] The preparation method of the core alloy is similar to that of Example 2, but the contents of Ti and B are increased to 8.0 wt % and 2.0 wt %, respectively. The preparation method of the shell alloy is exactly the same as that of Example 2.
[0210] (2) Electromagnetic field control of additive manufacturing process
[0211] The additive manufacturing process is exactly the same as in Example 2.
[0212] (3) Post-processing
[0213] The post-processing steps are the same as those in Example 2.
[0214] By comparing with Example 2, it can be observed that although the excessive Ti and B contents increase the volume fraction of the TiB2 phase, it also leads to the 2 The particle size is larger than the ideal 20-50nm range. This not only reduces the TiB 2 The strengthening effect may also lead to a decrease in the toughness of the material. 2 The phase will affect the diffusion and solid solution process of Cu-Mg elements, reducing the effect of solid solution strengthening. This comparison highlights the importance of accurately controlling the alloy composition in the present invention to achieve TiB 2 Optimal synergistic effect of nanophase and Cu-Mg solid solution strengthening.
[0215] Through these six comparative examples, the importance of the key innovations in the present invention, such as the double-layer composite wire structure, triaxial electromagnetic field control, reasonable process parameters, inert gas protection, post-treatment, and appropriate alloy composition, is fully verified. These comparative results strongly support the creativity and superiority of the present invention and provide important scientific basis and technical guidance for the development of high-performance aluminum-based composite materials.
[0216] In order to comprehensively evaluate the effectiveness and superiority of the present invention, a series of test experiments were designed. Experimental design and methods:
[0217] 1. Microstructure Analysis
[0218] First, the microstructure of the samples was analyzed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). SEM observations were performed using FEIQuanta 450FEG with an accelerating voltage of 20kV. TEM observations were performed using JEOL JEM-2100F with an accelerating voltage of 200kV. Sample preparation was performed using a precision ion milling system (PIPS). This analysis was intended to observe the size and distribution of the TiB2 nanophase and the solid solution of the Cu-Mg elements.
[0219] 2. Mechanical properties test
[0220] Secondly, tensile tests and hardness tests were performed. The tensile test was performed using an Instron 5967 universal testing machine with a tensile rate of 2 mm / min. The hardness test was performed using a Vickers hardness tester with a load of 500 g and a holding time of 15 s. These tests were designed to evaluate the strength, ductility, and hardness of the material.
[0221] 3. Electromagnetic field distribution simulation
[0222] Then, COMSOL Multiphysics software was used to numerically simulate the distribution of the triaxial electromagnetic field in the molten pool. The simulation parameters were based on actual process conditions, including the molten pool geometry, material conductivity and magnetic permeability, etc. This simulation helps to understand the mechanism of the influence of the electromagnetic field on the molten pool flow.
[0223] 4. Residual stress analysis
[0224] Again, the residual stress of the sample was measured by X-ray diffraction (XRD). A Bruker D8Advance diffractometer was used, with a Cu Kα radiation source, an operating voltage of 40 kV, and a current of 40 mA. The sin2ψ method was used for stress calculation. This analysis aims to evaluate the effect of electromagnetic field regulation on residual stress.
[0225] 5. Corrosion resistance test
[0226] Finally, an electrochemical corrosion test was conducted using a CHI660E electrochemical workstation in a 3.5wt% NaCl solution. A three-electrode system was used, with a saturated calomel electrode (SCE) as the reference electrode and a platinum electrode as the counter electrode. This test was designed to evaluate the corrosion resistance of the material.
[0227] Test results:
[0228] Table 1. Microstructure and mechanical properties test results
[0229]
[0230] Table 2. Residual stress and corrosion resistance test results
[0231]
[0232]
[0233] Based on the above test results, the following conclusions can be drawn:
[0234] 1. The best embodiment is embodiment 3, which shows the best performance in terms of strength, hardness and corrosion resistance. This is mainly due to its optimal TiB 2 Nanophase size (25nm) and distribution, as well as sufficient solid solution of Cu-Mg elements.
[0235] 2. The double-layer composite wire structure of the present invention (Examples 1-4) has significantly improved performance in various aspects compared to the single-layer structure (Comparative Example 1), which confirms the superiority of the double-layer structure.
[0236] 3. Compared with the uniaxial electromagnetic field (Comparative Example 2) or no electromagnetic field (Comparative Example 1), the triaxial electromagnetic field regulation (Examples 1-4) can more effectively control the size and distribution of the TiB2 nanophase, thereby obtaining better mechanical properties and corrosion resistance.
[0237] 4. Appropriate laser power and electromagnetic field intensity (Examples 1-4) can better balance strength and toughness compared to excessively high parameters (Comparative Example 3).
[0238] 5. Inert gas protection (Examples 1-4) can significantly improve the mechanical properties and corrosion resistance of the material compared to no protection (Comparative Example 4).
[0239] 6. Post-treatment, especially T6 heat treatment (Examples 1-4) can give full play to the effect of Cu-Mg solid solution strengthening and improve the comprehensive performance of the material compared with no post-treatment (Comparative Example 5).
[0240] 7. Reasonable control of Ti and B content (Examples 1-4) can obtain more ideal TiB than too high content (Comparative Example 6) 2 Nanophase size and distribution, leading to a better strength-toughness balance.
[0241] After in-depth analysis of these results, it is found that the present invention has the following unexpected technical effects:
[0242] 1. Synergistic strengthening effect: TiB 2 There is a significant synergistic effect between the nanophase and Cu-Mg solid solution strengthening. TiB 2 The nanophase not only plays a direct strengthening role, but also promotes the uniform distribution of Cu-Mg elements and enhances the solid solution strengthening effect. This synergistic effect makes the strength of the material exceed the simple superposition of a single strengthening mechanism.
[0243] 2. Adaptive microstructure: The three-axis electromagnetic field control creates a dynamic molten pool environment, making TiB 2 Nanophases and Cu-Mg elements can be distributed adaptively according to local cooling conditions. This adaptability significantly improves the uniformity and performance stability of the material.
[0244] 3. Residual stress control: The electromagnetic field regulation not only affects the microstructure, but also significantly reduces the residual stress of the material. This effect may be due to the electromagnetic field-induced molten pool convection, which promotes the uniform distribution of heat and reduces the local thermal gradient.
[0245] 4. Enhanced corrosion resistance: TiB 2 The uniform distribution of nanophase and the solid solution of Cu-Mg elements not only improve the mechanical properties of the material, but also significantly enhance the corrosion resistance. This may be due to the fact that TiB 2The nanophase forms a dense protective film on the surface of the material, while the Cu-Mg solid solution changes the electrochemical properties of the material.
[0246] 5. Expansion of process window: The method of the present invention significantly expands the preparation process window of high-performance aluminum-based composite materials by precisely controlling multiple process parameters. This means that the method has higher fault tolerance and adaptability, which is conducive to industrial production.
[0247] 6. Microstructure designability: By adjusting the composition of the double-layer wire, electromagnetic field parameters and post-processing process, the microstructure of the material can be precisely designed. This designability provides a new way to develop customized materials with specific properties.
[0248] In summary, the present invention realizes the synergistic effect of TiB2 nanophase reinforcement and Cu-Mg solid solution strengthening through innovative double-layer composite wire design and triaxial electromagnetic field regulation, and provides a new method for precisely controlling the microstructure of the material. This not only significantly improves the comprehensive performance of aluminum-based composite materials, but also provides an important technical basis for the development of a new generation of high-performance lightweight materials.
[0249] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. Double-layer composite wire and its electromagnetic field control additive manufacturing method for high-performance aluminum-based composite materials, characterized in that: The following steps are involved: (1) preparing a double-layer composite wire; (2) Using three-axis electromagnetic fields to control the additive manufacturing process; (3) Post-processing the prepared aluminum-based composite material.
2. The method according to claim 1, characterized in that The method for preparing the double-layer composite wire in step (1) comprises: (a) preparing a core alloy, comprising the following steps: First, a pure aluminum ingot with a purity of ≥99.99% is placed in a graphite crucible and heated to 700-750°C for melting under argon protection; Secondly, add a predetermined amount of titanium powder with a purity of ≥99.5% and boron powder with a purity of ≥99.5%, stir at a speed of 300-400 rpm, and keep for 30-60 minutes; Then, the melt is poured into a metal mold preheated to 200-250°C and cooled to room temperature; (b) preparing a shell alloy, comprising the following steps: First, a pure aluminum ingot with a purity of ≥99.99% is placed in another graphite crucible and heated to 700-750°C for melting under argon protection; Secondly, add predetermined amounts of copper particles with a purity of ≥99.9% and magnesium ingots with a purity of ≥99.9% in sequence, stir at a speed of 300-400 rpm, and keep stirring for 20-40 minutes; Then, the melt is poured into a metal mold preheated to 200-250°C and cooled to room temperature; (c) processing the core alloy and the shell alloy into round rods with a diameter of 8-10 mm respectively; (d) processing the shell alloy round rod into a hollow round tube having an inner diameter slightly larger than the diameter of the core alloy round rod; (e) inserting the core alloy round rod into the shell alloy hollow round tube to ensure that the two fit tightly; (f) placing the assembled double-layer structure in a vacuum hot isostatic pressing device at 500-550° C. and a pressure of 100-150 MPa for 2-4 hours; (g) The double-layer composite material after hot isostatic pressing is subjected to multiple hot extrusion and cold stretching to finally obtain a double-layer composite wire with a diameter of 1.2-1.6 mm.
3. The method according to claim 2, characterized in that The composition of the core alloy is: Aluminum: 92.5-96.0% by weight Titanium: 3.0-6.0% by weight Boron: 0.5-1.5 wt%.
4. The method according to claim 2, characterized in that: The composition of the shell alloy is: Aluminum: 93.0-96.5% by weight Copper: 2.5-5.0% by weight Magnesium: 1.0-2.5% by weight.
5. The method according to claim 1, characterized in that The step (2) of using a three-axis electromagnetic field to control the additive manufacturing process includes the following steps: (a) Equipment preparation: A fiber laser with a power of 1000-1500W is used as a heat source; Design and install a three-axis electromagnetic field generator that can independently generate a magnetic field strength of 0.2-0.5T in the x, y, and z directions; Prepare an additive manufacturing molding chamber with inert gas protection function; (b) Process parameter setting: Laser power: 800-1200W; Scanning speed: 600-1000mm / min; Wire feeding speed: 1500-2500mm / min; Layer thickness: 0.2-0.4mm; Argon flow rate: 15-25L / min; Substrate preheating temperature: 150-200℃; (c) Electromagnetic field parameter settings: X-axis magnetic field strength: 0.2-0.3T; Y-axis magnetic field strength: 0.3-0.4T; z-axis magnetic field strength: 0.4-0.5T; Magnetic field frequency: 10-50Hz; (d) Manufacturing process: First, the double-layer composite wire is loaded into the wire feeding device; Secondly, start the inert gas protection system to fill the molding chamber with argon gas; Then, preheat the substrate to a set temperature; Again, start the three-axis electromagnetic field system; Next, the laser scanning and wire feeding process begins to perform layer-by-layer deposition; After each layer is deposited, keep a cooling time of 20-30 seconds; Repeat the above process until the entire part is manufactured.
6. The method according to claim 1, characterized in that The post-processing in step (3) comprises the following steps: (a) Cool the manufactured parts to room temperature in an inert gas environment; (b) performing a T6 heat treatment, comprising: Solution treatment: 530-550℃, hold for 1-2 hours; Quenching: water quenching to room temperature; Aging treatment: 160-180℃, keep for 6-8 hours.
7. The method according to claim 6, characterized in that The method also includes the following control points: (a) TiB2 in-situ generation control: Reaction temperature: 700-750℃; Reaction time: 30-60 minutes; Stirring speed: 300-400rpm; Cooling rate:>50℃ / s; (b) Cu-Mg solid solution strengthening control: Solution treatment temperature: 530-550℃; Solution time: 1-2 hours; Quenching medium: water (temperature: 20-25°C); Aging temperature: 160-180℃; Aging time: 6-8 hours; (c) Electromagnetic field regulation: Magnetic field strength range: 0.2-0.5T; Magnetic field frequency: 10-50Hz; Magnetic field direction: x, y, z three-axis independent control; Magnetic field waveform: sine wave; (d) Porosity control: Inert gas purity: ≥99.999%; Gas flow rate: 15-25L / min; Molding chamber pressure: 1.1-1.2 standard atmospheres; Molten pool temperature: 660-720℃.
8. The method according to claim 7, characterized in that: The method further comprises the following steps: During the additive manufacturing process, after each layer of deposition is completed, an eddy current flaw detector is used to perform real-time non-destructive testing of the deposited layer with a detection frequency of 1-5MHz and a scanning speed of 50-100mm / s.
9. The method according to claim 8, characterized in that: The method further comprises the following steps: After T6 heat treatment, the obtained aluminum matrix composite material is subjected to surface treatment, including: First, sandblasting was performed using alumina sand with a particle size of 80-120 mesh and a sandblasting pressure of 0.4-0.6MPa; Secondly, anodization treatment was performed in a 20wt% sulfuric acid solution at a current density of 1-2A / dm 2 , the temperature is 18-22℃, the time is 30-60 minutes; Finally, seal the holes by soaking in boiling water for 15-30 minutes.
10. The method according to any one of claims 1 to 9, characterized in that: The method further comprises the following steps: During the additive manufacturing process, a high-speed camera is used to monitor the molten pool status in real time. The camera frame rate is 1000-2000fps and the resolution is not less than 1280x1024 pixels. The laser power and wire feeding speed are adjusted in real time based on the image analysis results, and the adjustment frequency is 10-20Hz.
Citation Information
Patent Citations
Method for preparing complex high strength aluminum alloy by adopting laser-induced electric arc additive manufacturing technology
CN107803503A
Device and method for electric arc double-wire additive manufacturing under action of external longitudinal magnetic field
CN113909635A
Electric arc fuse additive manufacturing method for low-porosity Al-Cu-Mg-Ag heat-resistant aluminum alloy component
CN116372319A
Alsimgmn alloy for additive manufacturing
US20240149348A1
Cited By
Gradient component preparation method of manganese-copper alloy with improved toughness
CN120485573A